The clinical presentation of monkeypox: a retrospective case-control study of patients with possible or probable monkeypox in a West London cohort. (January 2023) - Rimmer, Stephanie; Barnacle, James; Gibani, Malick M; Wu, Meng-San; Dissanayake, Oshani; Mehta, Ravi; Herdman, Trent; Gilchrist, Mark; Muir, David; Ebrahimsa, Umar; Mora-Peris, Borja; Dosekun, Olamide; et al.
Highlights: Human monkey pox virus (hMPXV) in this outbreak mostly affects males and those who self-identify as gay, bisexual, or men who have sex with men. Lymphadenopathy was associated with a higher likelihood of a positive result. Rash in hMPXV was more likely present in the genital or buttocks/perianal region. HIV positivity was not associated with an increased likelihood of positive hMPXV. Blood tests were not useful discriminators; rapid diagnostics are urgently needed. Abstract: Objectives: Since May 2022, cases of human monkeypox virus (hMPXV) with human-to-human cross-transmission have significantly increased in nonendemic countries. Our aim was to characterize diagnostic features of patients with confirmed and possible monkeypox to guide future risk stratification and to describe a virtual care model. Methods: We performed a retrospective case-control study of 140 patients assessed and screened for suspected monkeypox; on hMPXV polymerase chain reaction testing, 70 were confirmed positive, and 70 were negative. Data were compared to generate odds ratios of demographic and clinical features. Results: Patients who tested positive were predominantly cis-male (99%) and self-identified as gay, bisexual, and other men who have sex with men (94%). Lymphadenopathy at presentation was associated with a higher likelihood of a positive result (odds ratio [OR] 7.69 [95% confidence interval (CI) 3.58, 16.51]). Patients who tested positive were more likely to have a rash affecting the genital (OR 5.38 [95% CI 2.57, 11.23]) or buttocks/perianal region (OR 3.79 [1.70, 8.45]) than negative controls. A total of 79% of patients were engaged with a virtual ward follow-up. Conclusion: These data can inform a risk-based approach to the management of suspected monkeypox in gay, bisexual, and other men who have sex with men populations. Lymphadenopathy at presentation and the location of the rash were more associated with a positive hMPXV result. Health authorities can consider a virtual ward approach in the hMPHXV outbreak.